2009
DOI: 10.1093/hmg/ddp446
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a microRNA signature associated with progression of leukoplakia to oral carcinoma

Abstract: MicroRNAs (miRs) are non-coding RNA molecules involved in cancer initiation and progression. Deregulated miR expression has been implicated in cancer; however, there are no studies implicating an miR signature associated with progression in oral squamous cell carcinoma (OSCC). Although OSCC may develop from oral leukoplakia, clinical and histological assessments have limited prognostic value in predicting which leukoplakic lesions will progress. Our aim was to quantify miR expression changes in leukoplakia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
192
0
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(216 citation statements)
references
References 50 publications
14
192
0
10
Order By: Relevance
“…Those results suggested that the function of miR-181b may be unique, depending on the type of tumor and cellular context (29)(30)(31). It was previously demonstrated that miR-181b is a critical link between inflammation miR-181b as a key regulator of the oncogenic process and its clinical implications in cancer (Review) and malignant transformation (32). STAT3, a transcription factor activated by IL-6 (33-35), directly activates miR-21 and -181b-1 (36).…”
Section: Mir-181b Provides a Critical Link Between Inflammation And Cmentioning
confidence: 93%
“…Those results suggested that the function of miR-181b may be unique, depending on the type of tumor and cellular context (29)(30)(31). It was previously demonstrated that miR-181b is a critical link between inflammation miR-181b as a key regulator of the oncogenic process and its clinical implications in cancer (Review) and malignant transformation (32). STAT3, a transcription factor activated by IL-6 (33-35), directly activates miR-21 and -181b-1 (36).…”
Section: Mir-181b Provides a Critical Link Between Inflammation And Cmentioning
confidence: 93%
“…In fact, antisense inhibition of miR-21 leads to the induction of programmed cell death in neuroepithelial cells, through activation of caspases [159]. This apoptosis induction was also confirmed in breast cancer, colon cancer, pancreas cancer, lung cancer, liver cancer, prostate cancer, stomach cancer and oral squamous cell carcinoma (OSCC) [31,160,161,162,163]. So far, multiple targets of miR-21 have been identified and mapped to anti-apoptotic signalling pathways which suggest a promising miRNA treatment for cancer [31,164].…”
Section: Targeting Oncogenic Mirnasmentioning
confidence: 80%
“…It was found to be upregulated in cancer versus normal mucosa, while its expression changes in hyperplasia, dysplasia and cancer was not consistent across all patients, suggesting that its dysregulation could be different depending on the molecular subtype of OPL. 39 In other contexts, miR142-5p has been reported to play a role into macrophages differentiation 40 and to be down-regulated in glioblastoma-infiltrating macrophages. 41 Overall, the interaction between the immune system and neoplasia reflects a fundamental principle, applicable to all organ/cell types.…”
Section: Discussionmentioning
confidence: 99%